2015
DOI: 10.1177/0363546515587081
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet-Rich Plasma for Arthroscopic Repair of Medium to Large Rotator Cuff Tears

Abstract: Compared with repairs without PRP augmentation, the current PRP preparation and application methods for medium to large rotator cuff repairs significantly improved the quality, as evidenced by a decreased retear rate and increased CSA of the supraspinatus, but not the speed of healing. However, further studies may be needed to investigate the effects of PRP on the speed of healing without risking the quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
178
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(181 citation statements)
references
References 46 publications
0
178
1
2
Order By: Relevance
“…and thirteen provided the leukocyte concentration of the PRP used. The platelet concentration ranged from 1.7 to 8 times the baseline concentration, with a median value of 3.5 times the baseline concentration 4,21,22,26,[29][30][31] . Of the four studies in which the platelet concentration was #3.5, only one showed improved radiographic outcomes in association with PRP treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…and thirteen provided the leukocyte concentration of the PRP used. The platelet concentration ranged from 1.7 to 8 times the baseline concentration, with a median value of 3.5 times the baseline concentration 4,21,22,26,[29][30][31] . Of the four studies in which the platelet concentration was #3.5, only one showed improved radiographic outcomes in association with PRP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We identified seventeen studies investigating the use of PRP as an adjunct for surgical repair of rotator cuff tears [2][3][4][19][20][21][22][23][24][25][26][27][28][29][30][31][32] , including thirteen randomized controlled trials (RCTs); one prospective cohort study; two casecontrol studies; and one cohort study involving a retrospective control group. The number of patients ranged from twenty to eighty-eight.…”
Section: Rotator Cuff Tearsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other trials also found no significant differences in perioperative morbidity, clinical outcomes, or structural integrity when aPRP gel application was compared to a no-intervention cohort [34][35][36]. One group published two randomized trials comparing medium and large rotator cuff tears repaired with or without the addition of aPRP [37,38]. The trials included 48 and 74 patients, and shared similar trial designs, but differed slightly in their outcome measures.…”
Section: Orthopedicsmentioning
confidence: 99%